Setting up and managing the largest COVID-19 mass vaccination center in Lombardy, Italy - Calegari, Jessica Graziella; Bisesti, Alberto; Pazzaglia, Silvia; Gambazza, Simone; Binda, Filippo; Bruno, Martina; Chiappa, Laura; Piatti, Alessandra; Tiwana, Navpreet; Letzgus, Matteo; Castaldi, Silvana; Sottocorno, Marcello; et al. (Frontiers in Public Health, 2023)
Background. The rapid global spread of severe acute respiratory syndrome coronavirus (SARS-CoV-2) was met with the rollout of vaccination campaigns at mass vaccination centers. The Palazzo delle Scintille, Milan, was designated by the Lombardy regional administration as a vaccination site with the target of processing about 9000 users daily. Methods. For this observational study, we compared data on vaccinations delivered at the Palazzo delle Scintille with coronavirus disease (COVID-19)-related regional data. Results. Between 25 April 2021 and 28 February 2023, a total of 1,885,822 COVID-19 doses were administered; the mean hourly rate was 289 (247.2), the mean daily rate was 3185.5 (3104.5), the mean user age was 49.5 years (10.7). The Comirnaty vaccine (Pfizer-BioNTech) was most often given (1,072,030/1,885,822; 56.8%). Between 4 December 2021 and 15 January 2022, the daily dose rate was above the maximum daily capacity set by the regional administration. Conclusions. The trend for daily dose rates administered at the Palazzo delle Scintille center was in line with COVID-19-related regional data. The center played a major role in the regional mass vaccination campaign.